RETRACTED: The content of polyphenols in low-growing apple rootstocks depending on the type of soil in Central Russia - Zakharov Vyacheslav; Gulidova Valentina; Zubkova Tat'jana (E3S Web of Conferences, 2023)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001